Identification of a medicinal off-flavour in mineral water. - Strube, Andrea; Guth, Helmuth; Büttner, Andrea (Water Research, 2009)
The aim of the present study was to identify the compounds responsible for a characteristic medicinal off-odour in mineral water. 2-Dimensional high resolution gas chromatography-mass spectrometry analysis, in combination with olfactometry (HRGC-MS/O), led to the identification of 2-iodophenol and 2-iodo-4-methylphenol as the two compounds exhibiting the medicinal odour notes in mineral water. Determination of odour thresholds of these two compounds in air and water, as well as investigation of their odour characteristics in specific structure-odour activity assays, showed that 2-iodophenol and 2-iodo-4-methylphenol were both extremely potent odour substances with odour thresholds down to 0.03 and 0.0003ng/L air and 0.313 and 0.009mug/L water, respectively. The higher odour potency of 2-iodo-4-methylphenol suggests that this compound is primarily responsible for the medicinal off-odour. Furthermore, the same proportion of the panellists who were not able to detect the off-odour in mineral water exhibited drastically decreased sensibility to 2-iodo-4-methylphenol, but not to 2-iodophenol, which supports this hypothesis.<br